Congenital Heart Disease Does Not Increase Risk of Bacteremia In Children With Pneumonia - Azza K. Abdelmegeid; Sara S. Ragab; Fatma Al Zahraa Mostafa; Mai A. Hassan; Hala A. ElGindy (Pediatric Sciences Journal, 2021)
Background: Pneumonia is a major cause of childhood morbidity and mortality worldwide. It can be complicated by bacteremia. Congenital heart diseases (CHD) that cause increased pulmonary blood flow are a common predisposing factor for pneumonia in children. Aim of the Work: We aimed to identify if children with pneumonia suffer from bacteremia and to identify the most common organisms causing bacteremia in cases of pneumonia with and without congenital heart disease and to study role of CHD in influencing type of bacteremia in pneumonia. Patients and Methods: We conducted a pilot prospective study at Pediatric Hospital, Cairo University on 55 children with pneumonia (group 1) and 55 children with pneumonia and CHD (group 2). They all underwent complete blood counts, blood cultures and chest x-ray. Results: The frequency of bacteremia was 56.4% in children with pneumonia and no CHD and 38.2% in those with pneumonia and CHD. In group with pneumonia and no CHD blood culture results showed no growth in 24 cases (43.6%), Klebsiella spp. growth 11 cases (20%), Coagulase negative staphylococci (CONS) in 6 cases (10.9%), Methicillin Resistant Staphylococcus aureus in 4 cases (7.3%), Candida albicans in 2 cases (3.6%) and Pseudomonas spp. in 2 cases (3.6%). While the blood cultures in the group with pneumonia and CHD showed no growth in 34 cases (61.8%), Klebsiella spp. in 10 cases (18.2%), CONS in 5 cases (9.1%) and Candida albicans in 3 cases (5.5%) and no statistically significant difference was found. Conclusion: Frequency of bacteremia in children with pneumonia with and without congenital heart disease were not significantly different, the most common organism causing bacteremia in cases of pneumonia with or without congenital heart disease is Klebsiella spp < em>. and the most sensitive antibiotic is polymyxin.